Referral patterns and yield of computed tomography pulmonary angiography for suspected pulmonary embolism in a resource limited environment - Sefanyetso, Thato (My University, 2020)
INTRODUCTION: Pulmonary embolism is a common cause of morbidity and mortality despite advances in the diagnosis and treatment. There is increased utilization of CTPA (Computed Tomography Pulmonary Angiogram) despite the low yield for pulmonary embolism. AIM: To evaluate referral patterns and the outcome of CTPA in patients with suspected pulmonary embolus in our resource restricted environment in order to develop protocols for imaging practice.METHOD: The study population that met inclusion criteria was 132 patients. The primary investigator and two radiologists read CTPA images independently., noting the presence and severity of pulmonary embolism. The additional/alternate findings were also recorded. The presenting symptoms were found in the request forms and clinical files. HIV results and Ddimer concentrations were searched for in the NHLS computer system. RESULTS: Pulmonary embolism was found in 37% of patients and alternate findings seen in 73.8% of those with a negative CTPA result. CONCLUSIONS: Alternate findings are found in a significant number of patients with suspected pulmonary embolism. Clinical predictive scores and D-dimer levels could preclude the need for CTPA.
A research report submitted in fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020